A novel scalable audio coding scheme - Huan Zhou; Haiyan Shu; Rongshan Yu; Haibin Huang; Rahardja, Susanto (Proceedings of the ... IEEE International Conference on Acoustics, Speech and Signal Processing (1998), 2013)
A new scalable audio coding scheme is introduced in this paper. Its core idea is to create one additional scalability dimension during the encoding process for the purpose of generating a plural of scalable sub-bitstreams. Based on the multiple sub-streams, a smart truncator is designed that can truncate these sub-bitstreams with optimal rate-distortion (R-D) tradeoff. Benefited from the flexible R-D trade-off, the proposed new scheme could, within a wide bitrate range, outperform those traditional scalable coding schemes, which usually provides a fixed R-D relationship designed at a specified bitrate. To verify the performance, the proposed scheme is further implemented based on a prior art scalable audio codec. Significant quality improvement is observed from the new codec via a series of subjective listening tests.